2014
DOI: 10.1111/bph.12557
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of inflammasome activation improves the impaired pattern of healing in genetically diabetic mice

Abstract: Type 2 diabetes impairs the healing process because of an exaggerated and persistent inflammatory response, and an altered expression pattern of angiogenic molecules. We investigated the effects of inflammasome blockade in diabetes-related wound-healings defects, in genetically diabetic mice. EXPERIMENTAL APPROACHAn incisional skin wound model was produced on the back of female diabetic C57BL/KsJ-m +/+ Lept db mice (db i.p.), or Brilliant Blue G (BBG, 45.5 mg·kg −1 i.p.), or vehicle. Mice were killed on 3, 6 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 27 publications
4
60
0
Order By: Relevance
“…Targeting the (NLRP)-3 inflammasome may be particularly useful for reducing inflammation in diabetes since its activation under chronic hyperglycemic states has been shown to initiate an intracellular inflammatory cascade that promotes a persistent pro-inflammatory state (Zhou, Tardivel et al 2010). In addition, diabetes–mediated metabolic syndrome induces accumulation of lipid activators that facilitate assembly of the (NLRP)-3 inflammasome leading to activation of caspase-1 and increased secretion of IL-1β and IL-18, both pro-inflammatory factors, which exacerbate systemic inflammation and insulin resistance (Bitto, Altavilla et al 2013). …”
Section: Sulfonylureasmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting the (NLRP)-3 inflammasome may be particularly useful for reducing inflammation in diabetes since its activation under chronic hyperglycemic states has been shown to initiate an intracellular inflammatory cascade that promotes a persistent pro-inflammatory state (Zhou, Tardivel et al 2010). In addition, diabetes–mediated metabolic syndrome induces accumulation of lipid activators that facilitate assembly of the (NLRP)-3 inflammasome leading to activation of caspase-1 and increased secretion of IL-1β and IL-18, both pro-inflammatory factors, which exacerbate systemic inflammation and insulin resistance (Bitto, Altavilla et al 2013). …”
Section: Sulfonylureasmentioning
confidence: 99%
“…Glyburide treatment also induced concurrent increased expression of pro-healing IGF-1, TGF-β, and IL-10 growth factors (Mirza, Fang et al 2014). Separate confirmatory studies using local wound treatment of incisional wounds in diabetic db/db mice with the I-κB kinase-β inhibitor, BAY 11-7082, which also inhibits the (NLRP)-3 inflammasome, showed improved wound healing and increased angiogenesis with upregulation of VEGF and SDF-1α (Bitto, Altavilla et al 2013). …”
Section: Sulfonylureasmentioning
confidence: 99%
“…126 In another study with material from both humans and mice, it was postulated that the NLRP3 inflammasome may be continually ac-tivated within the macrophages present in the wounds of diabetic patients, and that this contributes to the difficulty of wound healing. 127 By contrast, another study conducted with mice showed that the NLRP3 inflammasome would be important in the initial stage of the healing process.…”
Section: Dermatological Diseases Associated With Inflammasomesmentioning
confidence: 99%
“…An in vivo study has shown that activation of the NLRP3 inflammasome is one of the key contributors to the delayed healing of wounds in diabetic mice [13]. To further access the inflammatory response mechanism in diabetic wounds, we hypothesized that stimulation with high glucose following a pro-inflammatory signal would lead to autophagy inhibition, reactive oxygen species (ROS) production and eventually to activation of the Nod-like receptor protein (NLRP) -3.…”
Section: Introductionmentioning
confidence: 99%